Antifungal activity of Bacillus species Isolated from Soil Samples of Nepal against Aflatoxin Producing Aspergillus spp - Sharma, Suprina; Joshi, Dev Raj; Poudel, Pramod; Sharma, Supriya; Karki, Tika Bahadur; Tuladhar, Reshma (Journal of Institute of Science and Technology, 2025)
In Nepal, improper storage of staple foods leads to contamination by aflatoxin-producing molds, posing serious health risks like liver cancer. Farmers, unaware of these dangers, often use unsafe chemicals for prevention, while biological control using Bacillus spp., a proven, safe, and multifunctional alternative, remains unexplored. This study aims to isolate native Bacillus species capable of inhibiting Aspergillus flavus growth and detoxifying aflatoxins, offering a sustainable solution. A total of 50 samples (40 soil samples, 5 compost and 5 food samples) were randomly collected from different places of Nepal. Bacillus. spp were selectively isolated by heating the samples at 80⁰C for 10 minutes. The isolates were identified by standard microbiological techniques. Growth inhibition of A. flavus by Bacillus. spp was done by dual-culture technique on potato dextrose agar. Isolates showing high inhibitory effect against A. flavus were further identified by 16S rRNA gene sequencing. Altogether 51 isolates were presumptively identified as Bacillus species. Five isolates, Bacillus subtilis, B. tequilensis, B. licheniformis, B. cereus, B. weidmannii effectively inhibited the growth of aflatoxigenic A. flavus. These potent Bacillus strains will have implication in the commercial production of bioactive anti-aflatoxigenic compound to minimize the postharvest contamination of the crops.